1998
DOI: 10.1016/s0022-5223(98)70018-2
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 derived from hypoxic myocytes promotes neutrophil-mediated reperfusion injury in myocardium

Abstract: Interleukin-6 is produced from myocardium during ischemia and reperfusion in patients undergoing coronary bypass grafting. This interleukin-6 may be derived from hypoxic myocytes and play a role in neutrophil-mediated reperfusion injury in myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 16 publications
3
77
0
2
Order By: Relevance
“…IL6 secretion has been demonstrated to be facilitated by hypoxia in human umbilical vein and pulmonary endothelial cells, primary human pulmonary fibroblasts and vascular smooth muscle cells, and Kupffer cells as well as whole pulmonary artery organoid cultures (Yan et al, 1995(Yan et al, , 1997Tamm et al, 1998;Ziesche et al, 1996;Kotake-Nara et al, 2005;Sawa et al, 1998;Hartmann et al, 2000). Our previous studies found that the level of IL-6 was increased in pulmonary tissues of rats with hypoxia-induced pulmonary hypertension .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…IL6 secretion has been demonstrated to be facilitated by hypoxia in human umbilical vein and pulmonary endothelial cells, primary human pulmonary fibroblasts and vascular smooth muscle cells, and Kupffer cells as well as whole pulmonary artery organoid cultures (Yan et al, 1995(Yan et al, , 1997Tamm et al, 1998;Ziesche et al, 1996;Kotake-Nara et al, 2005;Sawa et al, 1998;Hartmann et al, 2000). Our previous studies found that the level of IL-6 was increased in pulmonary tissues of rats with hypoxia-induced pulmonary hypertension .…”
Section: Discussionmentioning
confidence: 94%
“…A number of studies have demonstrated that secretion of interleukins is facilitated by hypoxia (Yan et al, 1995(Yan et al, , 1997Tamm et al, 1998;Ziesche et al, 1996;Kotake-Nara et al, 2005;Sawa et al, 1998;Hartmann et al, 2000). Several studies have also indicated that Janus kinases (JAKs) and signal transducers and activators of transcription (STATs) are activated by interleukin 6 (IL6) in cardiomyocytes, macrophages, carcinoma cells and neurons and by hypoxia in pulmonary arterial smooth muscle cells, rat cardiomyocytes, retinal microvascular endothelial cells (Negoro et al, 2001;Mascareno et al, 2005;Wang et al, 2005;Dawn et al, 2004;Lee et al, 2006;Yamauchi et al, 2006;Terrell et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…After binding to its receptor, IL-6 elicits numerous effects including antibody induction, hematopoiesis, thrombocytopoiesis, and acute-phase protein synthesis (1,2). Significant increases in serum levels of IL-6 and its mRNA and protein expression in cardiac tissues have been reported in patients with several cardiac diseases including congestive heart failure (3-5), myocarditis (3), septic cardiomyopathy (6), myocardial infarction (7)(8)(9), cardiac myxoma (10), and the cell injury associated with ischemia/reperfusion (11) and cardiopulmonary bypass (12). Thus, IL-6 has been suggested to play an important role in the pathophysiology of these cardiac disorders.…”
Section: Il-6mentioning
confidence: 99%
“…[57][58][59][60] In the myocardial ischemia-reperfusion model, Kukielka et al 59 showed that IL-6 played an important role in the induction of ICAM-1 in the ischemic regions. Regarding the clinical study also, Ohtsuka et al 61 clearly showed that serum levels of (c) and (d) Specimens from the border region between nonischemic and ischemic myocardium exposed to 30 min of ischemia followed by 3 h of reperfusion.…”
Section: Discussionmentioning
confidence: 99%